Providence - David Fergusson (St Andrews Encyclopaedia of Theology, 2022)
Though not linguistically prominent in Christian scripture, the theology of providence captures several recurring scriptural themes. These include the order of the cosmos, the wisdom reflected in the natural and social worlds, the direction of the history of Israel and the church, and the coming of Christ into the world. Under the influence of Platonic and Stoic philosophy, Christian theologians borrowed and adapted the language of providence to articulate some key tenets of their faith. Providence was personalized to stress the parental care of God for each individual, and aligned to a divine purpose with eschatological outcomes, albeit with some discernable differences between Greek and Latin approaches, particularly regarding fate and freedom. The later systematization of providence was developed in the Latin West during the Middle Ages, particularly the distinction between primary and secondary causality which sought to explain how a world of contingent causal forces could be viewed as expressing in every respect the will of God. Foregrounded in the Reformed churches, this same teaching was developed into a threefold form of providence in terms of preservation, concurrence, and government. Following the Enlightenment, accounts of providence were inflected to align with natural science, Deism, the nation state, and colonial expansion. With perceived problems around divine determinism, creaturely freedom, the problem of evil, and following shattered narratives of progress, modern theology has sought to revise traditional accounts in a more cautious and chastened manner. Several competing approaches can now be discerned in contemporary confessional studies of divine providence.